Custom prosthetic reconstruction of proximal tibial giant cell tumor - Shailendrasingh Thakur; C M Badole; Kiran Wandile (Wolters Kluwer Medknow Publications, 2014)
Giant cell tumor (GCT) also called osteoclastoma of bone is the most common bone tumor encountered by an orthopedic surgeon. GCT generally occurs in skeletally mature individuals with peak incidence in the third decade of life. Less than 5% are found in patients with open physis and only about 10% of cases occur in patients older than 65 years. We present a case of proximal tibia GCT managed with custom mega prosthetic arthroplasty.